L’anxiete langagiere en classe de français : les attitudes des lyceens polonais envers l’enseignement/apprentissage de l’oral - Lipińska, Julia (Neofilolog, 2021)
<span class="NormalTextRun SCXW128187869 BCX0" data-ccp-parastyle="Treść A" data-ccp-parastyle-defn="{"ObjectId":"e51c33b8-d8e0-4a98-baba-1aafee078940|242","ClassId":1073872969,"Properties":[134233614,"true",201340122,"2",201341983,"0",268442635,"24",335551500,"0",335551547,"1036",335551550,"6",335551620,"6",335559731,"709",335559740,"360",469769226,"Times New Roman,Arial Unicode MS",469775450,"Treść A",469777841,"Times New Roman",469777842,"Arial Unicode MS",469777843,"Arial Unicode MS",469777844,"Times New Roman",469778129,"TreA"]}">While learning a foreign language, students have to practice speaking through different activities in class. Unfortunately, speaking is often a challenge for students not only due to linguistic difficulties, but most importantly because of the stress caused by talking in a foreign language in front of their classmates. This phenomenon, called language anxiety, makes it impossible for some students to participate actively and thus to develop their speaking abilities. It is therefore important to understand which types of tasks cause the highest anxiety levels, as well as to find out what can help students overcome their anxiety. To answer these questions, we led a research among Polish high school students learning French. They were asked about their attitudes towards different speaking activities in class, as well as about the atmosphere in class. The results show students are the most stressed while speaking in front of their peers and prefer interaction in small groups. Language games also appear to lower the level of anxiety during speaking. In addition, positive atmosphere and lack of judgment help students overcome their fear, but they do not eliminate it completely for every person.